Integrasi Imtak dan Iptek: Landasan dan Faktor Kunci Sukses Penerapannya dalam Pendidikan Islam - Fatimah Fatimah; Endah Winarti (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2022)
The goals of education in Indonesia are aligned with the goals of Islamic education, namely directing efforts to form perfect humans or Muslims, by developing their potential in the cognitive, affective and psychomotor domains. On implementation. For educational institutions, efforts to achieve these goals provide an opportunity for the emergence of the concept of developing an Islamic Religion education curriculum that leads to how to integrate the teaching of faith and piety (imtak) with science and technology (science and technology). This article reviews the foundation on which the integration effort is based and the key driving factors for the successful implementation of this integration. The results of the study show that there are five implementation bases: religious, philosophical, juridical, psychological and socio-economic. Meanwhile, the key success factors include: educators & education staff, availability of textbook teachers, and supportive extracurricular activities